Hubungan Kadar Albumin, Limfosit, dan Komorbiditas dengan Lama Rawat Inap - Aisy Samara Istiqomah; Wiwit Agung Sri Nur Cahyawati; Roselina Panghiyangani (Homeostasis, 2022)
Abstract: Hypoalbuminemia is common in the elderly patients. Along with aging there is a decrease in physiological functions including the immune system which causes lymphopenia. Comorbidities also increase significantly with age. This research is analytic observational with cross-sectional method aimed to analyze the correlation of albumin, lymphocytes, and comorbidities with the length of stay of elderly patients. The research sample of 31 elderly people was obtained using a total sampling technique according to the inclusion and exclusion criteria. The mean albumin level was 3.07±0.61 gr/dl. The mean lymphocyte value was 17.84±9.68 %. The median comorbidity score was 2 with a minimum was 0 and the maximum was 4. The average length of stay for elderly patients was 7±3.84 days. There is a significant correlation between lymphocytes and LOS in elderly patients (r=-0,45;p=0,011). There is a significant correlation between comorbidities and LOS in elderly patients (r=0,368;p=0,042). There is no correlation between albumin and LOS of elderly patients (p>0.05) in the Internal Medicine Ward at Ulin Hospital Banjarmasin. Keywords: albumin levels, lymphocyte, comorbidity, length of stay, elderly Abstrak: Hipoalbuminemia umum ditemukan pada lansia. Seiring dengan peningkatan usia terjadi penurunan fungsi fisiologis termasuk pada sistem imunitas yang pada akhirnya menyebabkan limfopenia. Komorbiditas pun meningkat secara signifikan seiring bertambahnya usia. Penelitian ini bersifat observasional analitik dengan metode cross-sectional dan bertujuan untuk menganalisis korelasi albumin, limfosit, dan komorbiditas dengan lama rawat inap pasien lansia. Sampel penelitian sejumlah 31 lansia diperoleh menggunakan teknik total sampling sesuai kriteria inklusi dan eksklusi. Rerata kadar albumin 3,07 gr/dl±0,61. Rerata nilai limfosit 17,84%±9,68. Median skor komorbiditas didapatkan skor 2 dengan minimal 0 dan maksimal 4. Rerata lama rawat inap pasien lansia adalah 7±3,84 hari. Terdapat korelasi signifikan antara limfosit dan lama rawat pasien lansia (r=-0,45; p=0,011). Terdapat korelasi signifikan antara komorbiditas dan lama rawat pasien lansia (r=0,368; p=0,042). Tidak terdapat korelasi antara albumin dengan lama rawat pasien lansia (p>0,05) di Ruang Rawat Penyakit Dalam RSUD Ulin Banjarmasin. Kata-kata kunci: kadar albumin, limfosit, komorbiditas, lama rawat inap, lansia